2013
DOI: 10.1080/15287394.2013.836694
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Mine Proximity, Immune Function, andHelicobacter pyloriInfection in Tajikistan

Abstract: Tajikistan is a country with numerous abandoned uranium mines and individuals residing in close proximity to these sites. Inspection of one of these sites next to the town of Taboshar revealed uncontrolled waste with elevated radiation levels. Convenience samples of subjects likely to have been exposed to uranium mining (i.e., combined living near wastes and former miners) and unexposed subjects (living far from mines and never working in mining) were recruited. There was a higher prevelance of Helicobacter py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Health consequences such as increased risk of cancer, cardiovascular disease, inflammation and immune dysregulation have been associated with environmental exposure to metals such as arsenic and uranium [ [8] , [9] , [10] , [11] ]. Studies have shown that populations living near AUMs have an increased likelihood of developing multiple chronic diseases [ [12] , [13] , [14] , [15] ]. Additionally, uranium consumption through drinking water is associated with increased detection of autoantibodies to native DNA and/or chromatin [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Health consequences such as increased risk of cancer, cardiovascular disease, inflammation and immune dysregulation have been associated with environmental exposure to metals such as arsenic and uranium [ [8] , [9] , [10] , [11] ]. Studies have shown that populations living near AUMs have an increased likelihood of developing multiple chronic diseases [ [12] , [13] , [14] , [15] ]. Additionally, uranium consumption through drinking water is associated with increased detection of autoantibodies to native DNA and/or chromatin [ 16 ].…”
Section: Introductionmentioning
confidence: 99%